The Dynamics of Rebuilding Trust and Trustworthiness in Marital Relationship Post Infidelity Disclosure - Pramudito, Anselmus Agung; Minza, Wenty Marina (Faculty of Psychology, Universitas Gadjah Mada, 2021)
Infidelity has been one of the leading causes of marital divorce for couples in many countries, including Indonesia. For couples surviving infidelity in marriage, some aspects of the marital relationship such as trust and trustworthiness can be affected. Rebuilding trust and trustworthiness after the disclosure of infidelity can be one of the most important factors in recovering the quality of marital relationship. This research adopted qualitative research method with phenomenological approach to explore the dynamics of rebuilding trust and trustworthiness in marital relationship post infidelity disclosure. The study found that the victim of infidelity rebuilt their trust toward the perpetrator in five aspects. Three of these were personal aspects, including risk identification and prevention, predictability, and belief; and two were relational aspects, including intimacy and reciprocity. Whereas the perpetrators of infidelity rebuilt their trustworthiness by showing four aspects: commitment, openness and honesty, benevolence, and religiosity. Those aspects provided implications in recovery of marital relationship post infidelity disclosure.